High-performance Cuk converter with turn-on switching at zero voltage and zero current - Basim Talib Kadhem; Khalid M. Abdulhassan; Sumer S. Harden (Bulletin of Electrical Engineering and Informatics, 2023)
The soft-switching technique has the potential to significantly enhance the performance of the power converter. This is primarily because it allows for an increase in the switching frequency, which ultimately leads to improved modulation quality. This raises extra concerns, particularly in high-power applications, because in a standard hard-switching converter structure, components can often not function at frequencies higher than a few hundred hertz. This paper presents a high-efficiency soft switching CUK converter.When the main and auxiliary switches are turned on and off at zero voltage, the proposed converter yields zero voltage and zero current. The suggested method is ideal for a DC-DC converter based on IGBTs or MOSFETs. The recommended systems are described using theoretical analysis, the results of computer simulations, and experimental data derived from a prototype. The design parameters of the inductance and capacitor circuit for edge-resonant soft switching were obtained using the output power and the switching duty ratio. In the end, soft-switching is better than hard-switching in terms of efficiency, particularly when operating under full load.